PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN EKSPOSITORI TERHADAP HASIL BELAJAR MATEMATIKA DITINJAU DARI KEMAMPUAN AWAL MATEMATIKA DI MADRASAH ALIYAH NEGERI TAPANULI SELATAN - Hasibuan, Abdul Hamid (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
This research is quantitative research form design quasi experiment Which used control class and experimental class. The experimental class applies PBL and Expository models in the learning process with SPLTV material. The population in this study were all class X students at MAN Tapsel. The sample in this study was 20 students for each control class and experimental class using a non-probability sampling design with purposive sampling type . Using the PBL type cooperative learning model, the average student score was 58.66 to 82.16. For the Expository type cooperative learning model, the student average was 58.16 and was 81.84. Meanwhile, in the control class, the pre-test score was 58.5 and the post-test score was 70.34. In the ANOVA test, the sig value < 0.05, namely 0.006 < 0.05 and the calculated F value > F table , namely 5.694 > 3.59. It can be concluded that these three methods equally influence students' mathematics learning outcomes. From the activities, the best was the class that used the PBL model , namely 82.16, followed by the class that applied Expository with an average of 81.99. Keywords : Learning Outcomes, PBL, Expository.